BIOKONSENTRASI LOGAM KADMIUM (Cd) DALAM JARINGAN REMIS (Corbicula sp.) TERHADAP LINGKUNGAN ABIOTIK (AIR DAN SEDIMEN) DI PERAIRAN SUNGAI MUSI KOTA PALEMBANG - Emilia, Ita (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2015)
This study aims to determine the level of bioaccumulation of metals cadmium (Cd) in mussel ( Corbicula sp.) based on the value of bioconcentration factor (BCF). The sampling method was purposive sampling methode. The study site was divided into eight stations, obtained the following results, Bioconcentration Factor ( BCF ) of Cd metal in mussel (Corbicula sp.) and water ranged 38.2301 - 315.2381 with an average of 101.0334, indicated Cd metal bioaccumulation in the mussel (Corbicula sp.) and water accumulated in the medium category. BCF value metals Cd in mussel ( Corbicula sp.) and sediment ranged 2.2857-8.0940 with an average of 4.7931 indicates Cd metal bioaccumulation in the mussel (Corbicula sp.) and sediment accumulated in the lower category . Key words : Bioconcentration , Cadmium , Water , Sediment , Mussels , Musi River